2011
DOI: 10.1093/molbev/msr302
|View full text |Cite
|
Sign up to set email alerts
|

Cost of Antibiotic Resistance and the Geometry of Adaptation

Abstract: The distribution of effects of beneficial mutations is key to our understanding of biological adaptation. Yet, empirical estimates of this distribution are scarce, and its functional form is largely unknown. Theoretical models of adaptation predict that the functional form of this distribution should depend on the distance to the optimum. Here, we estimate the rate and distribution of adaptive mutations that compensate for the effect of a single deleterious mutation, which causes antibiotic resistance. Using a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
97
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 78 publications
(107 citation statements)
references
References 50 publications
(109 reference statements)
8
97
2
Order By: Relevance
“…In such experiments, the fitness of replicate populations reaches a plateau [which may sometimes vary (Schoustra et al 2009)] or at least shows a striking deceleration. Consistent with this finding, negative epistasis among beneficial mutations has been repeatedly reported: beneficial mutations tend to be less advantageous when arising from fitter parents (MacLean et al 2010;Chou et al 2011 ;Khan et al 2011;Sousa et al 2011). These observations are obviously suggestive of the existence of an optimum for fitness, at some local scale at least.…”
Section: Practical Illustrationssupporting
confidence: 60%
See 3 more Smart Citations
“…In such experiments, the fitness of replicate populations reaches a plateau [which may sometimes vary (Schoustra et al 2009)] or at least shows a striking deceleration. Consistent with this finding, negative epistasis among beneficial mutations has been repeatedly reported: beneficial mutations tend to be less advantageous when arising from fitter parents (MacLean et al 2010;Chou et al 2011 ;Khan et al 2011;Sousa et al 2011). These observations are obviously suggestive of the existence of an optimum for fitness, at some local scale at least.…”
Section: Practical Illustrationssupporting
confidence: 60%
“…In principle, the FGM can be used to predict how the DFE is affected by any environmental or genotypic context (epistasis), with any type of nonsilent mutation. Empirical support of the model's predictions has recently accumulated (Martin and Lenormand 2006a,b;Martin et al 2007;MacLean et al 2010;Sousa et al 2011;Weinreich and Knies 2013), although it was sometimes relatively indirect. The most quantitative tests (Martin et al 2007;MacLean et al 2010;Sousa et al 2011), and hence those with most statistical power, used the model to predict how the DFE is affected by epistasis.…”
Section: "Heuristic" Landscapesmentioning
confidence: 98%
See 2 more Smart Citations
“…Previous work with an earlier generation of these mutant lines (and the mutant lines of several other A. thaliana ecotypes) suggested that beneficial mutations occurred, but that the magnitude of deleterious mutations was greater (Stearns & Fenster, 2016). This study, when considered in the context of the previous A. thaliana mutation accumulation studies, suggests that high magnitude deleterious mutations are more common than high magnitude beneficial mutations and that adaptation likely occurs due to small or intermediate effect beneficial mutations, as suggested by Fisher (1930) and Kimura (1983) and supported experimentally (Barrett, MacLean, & Bell, 2006; Heilbron et al., 2014; Sousa, Magalhaes, & Gordo, 2012). The large deleterious mutations that may be affecting these lines would likely be removed from the population via selection and would not contribute significantly to standing genetic variation.…”
Section: Discussionmentioning
confidence: 99%